Perspectives on Afghan Refugee identity in Pakistan - Muhammad Najam ud din Farani (Journal of Political Studies, 2020)
Afghan refugees in Pakistan are a classical example of refugee-war nexus. They have been historically conditioned by wars and internal conflicts inside Afghanistan. The conflict within Afghanistan which has historically conditioned Afghan refugees has spanned for more than four decades. This study is an attempt to contextualize history, demographics, institutes, national policy and different factors that have conditioned the identity of Pakistani Afghan refugee community. This study also attempt to explore different perspectives on the identity of Afghan refugee community inside Pakistan